Kinetic Model Comparison for Biogas Production from Poultry Manure and Banana Peels. Issue 2 (2020) - Nwosu-Obieogu, Kenechi; Aguele, Felix Osarumehnsen; Onyenwoke, Austin; Adekunle, Kayode
No abstract available